Upaya Pembentukan Karakter Peserta Didik Di Sekolah Melalui Kegiatan Ekstakurikuler Pramuka - Moh. Miftahul Arifin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The multi-dimensional crisis that has hit this nation has provided a new discourse to prepare a very crucial step to be operationalized in the life of this nation, especially the next generation, namely character education. Character education is implemented in schools from elementary school to college level. The Scout Movement is an educational movement for young people, voluntary, non-political, open to all, regardless of origin, race, ethnicity, and religion, which organizes scouting through a value system based on Satya and Darma Pramuka. Based on that understanding, schools should organize scouting as a fun educational process for young people, under the responsibility of adult members, which is carried out outside the school and family educational environment, with specific objectives, basic principles, and educational methods. Scouting education as extracurricular activities in primary to secondary schools refers to Permendikbud No.81A of 2013. In addition, there are regulations in Law No. 12/2010, which regulate the implementation of scouting education. In addition, there is a regulation in Law Number 12 the Year 2010, which regulates the implementation of scouting education. In the implementation of the 2013 curriculum, scouting extracurricular activities can be implemented in 3 models, namely: (1) Block system which is implemented at the beginning of school entry; (2) Actualization System, the learning process of each subject into Scouting Education; and (3) Regular System for students who have an interest and interest in becoming a member of the scout. Revitalization of the scout movement needs to be done so that scouting activities can be held in higher quality, attract interest and become the choice of students, and create students with strong characteristics to become future leaders of the nation in various fields of life. In order to support and strengthen these policies, planning of scout extracurricular activities is absolutely necessary.